2020
DOI: 10.1007/s00428-020-02976-5
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 immunohistochemistry in non-small-cell lung cancer: unraveling differences in staining concordance and interpretation

Abstract: Programmed death ligand 1 (PD-L1) immunohistochemistry (IHC) is accepted as a predictive biomarker for the selection of immune checkpoint inhibitors. We evaluated the staining quality and estimation of the tumor proportion score (TPS) in non-small-cell lung cancer during two external quality assessment (EQA) schemes by the European Society of Pathology. Participants received two tissue micro-arrays with three (2017) and four (2018) cases for PD-L1 IHC and a positive tonsil control, for staining by their routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…While the former is largely unpredictable, the latter should be standardized by following strict laboratory protocols [167]. However, differences in staining concordance and interpretation may occur among various institutes [166,174]. Recently, Angels et al [175] reported a significant rate of suboptimal PD-L1 immunostaining (clones SP142 and SP263) in tonsillectomy specimens exposed to more than 72 h in formaldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…While the former is largely unpredictable, the latter should be standardized by following strict laboratory protocols [167]. However, differences in staining concordance and interpretation may occur among various institutes [166,174]. Recently, Angels et al [175] reported a significant rate of suboptimal PD-L1 immunostaining (clones SP142 and SP263) in tonsillectomy specimens exposed to more than 72 h in formaldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…We do not know how many of the laboratories included in our study participated in PD-L1 external quality assessment (EQA) schemes during the study period. Potentially, participation of all laboratories in such EQA schemes could help in reducing interlaboratory variation in PD-L1 positivity [48]. Also, when LDTs are used for PD-L1 staining, it is paramount that these LDTs are optimized and validated sufficiently [49].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the use of commercial kits results in a better staining performance compared to LDTs [ 16 , 56 ]. Nonetheless, essential for an optimal staining score is a validated protocol obtaining a good staining quality, while paying attention to interpretation competence of the pathologist to reduce inter-individual variation and avoiding misclassification/misinterpretation [ 15 , 16 , 57 , 58 ]. In addition, accreditation also had a positive impact on staining performance and interpretation for these biomarkers [ 55 ].…”
Section: The Scientific Value Of Eqa Schemes and Importance For Indus...mentioning
confidence: 99%
“…In addition, EQA has proven its benefit for by creating the opportunity to set up collaborations with the EQA provider to investigate the use and performance of their kits. Previous EQA research has shown that EQA participation can reveal flaws in testing methods, for example essential differences between staining techniques [ 15 , 16 ]. In addition, EQA schemes, as well as ring studies, have had a supporting role in the development of best practice guidelines by highlighting pitfalls and common errors [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%